(The Study of Glucomannan Extraction from Iles-Iles (Amorphophaalus spp) and its Application on Food Product - Hawani Lubis, Enny; Djubaedah, Endah; Alamsyah, Rizal; Noerdin NK, Moch (Warta Industri Hasil Pertanian, 2004)
The study was aimed at investigating the method of glucomannan extraction from iles-iles and its use application as konyaku. The extraction can be done through mechanical and chemical process. iles-iles were canned and sliced into small chips withÂ  mm thickness. natrium sulfite of 1000 ppm was added during 15 minutes and continuted by soaking them with CaCO3 (2,5%, 5%, and 7,5). The chips was then sun dried for 25-30 hours and continued with oven drying on 60 C temperature and 16 hours. the chips were ground to produce iles-iles flour. Glucomannan flour was them separated from iles-iles flour by chemical separation process using sieve where the lighter one will pass through the sieve, while the mannan will remain on the sieve. A blower was also used to separate glucomannan from calcium oxalate and the remaining cll wallof iles-iles. The chemical separation of glucomannan flour from iles-iles was conducted by water extraction at 55 C. The ethanol of 95% was added to the extract to obtain mannan layer which then was oven dried.